Aspectos envolvidos na sustentabilidade do serviço de gerenciamento da terapia medicamentosa - Aline Angélica de Souza Valentin (2020)
Comprehensive Medication Management (CMM) presents positive clinical, humanistic and economic results in several scenarios, and studies have already elucidated the components necessary for its implementation. Despite this, most initiatives are still unsuccessful in maintaining the long-term provision of the service. Thus, this study aimed to understand the elements that contribute to the consolidation and continuation of the CMM service. The chosen methodology was the ground theory. In the period from May 2019 to February 2020, semi-structured interviews were conducted with 8 pharmacists and 4 managers who experienced the offer of CMM in various scenarios of public and private health in Belo Horizonte and the metropolitan region. Records in the researcher's field diaries and document analysis were also used. After systematic analysis of the data, as recommended by the grounded theory, three determinant categories were identified in the CMM sustainability process. The first one, called “Collaborative care is essential: You can't think of CMM just like the pharmaceutical and patient dyad”, which addresses the essentiality of professional partnerships to strengthen the service. The second category, “Negotiating the sustainability of the CMM”, evaluates important elements about service management. And the third, “Who will pay for the service?”, analyzes the possibilities of financial resources in health systems. The results revealed that the consolidation of CMM services is a strategic process, which requires careful planning that begins with the implementation of the service.